Identification of Potential Risks and Controlling Factors Associated with Helicopter Operation: A Mix-Method Investigation from Oil and Gas Industries (International Journal of Integrated Engineering, 2019)
This research article focuses on the identification of the characteristics of potential hazards and their suitable controlling factors for offshore helicopter operation at Malaysia and Saudi Arabia oil and gas drilling domains. In this study explanatory (Quantitative Leading to Qualitative) research design has been used for data collection and analysis process. While, 160 respondents for quantitative and 06 respondents for quantitative research has been participated in this study from targeted industries of Malaysia and Saudi Arabia. Likewise, descriptive statistical approach (Mean, Standard Deviation and Percentage) has been adapted for quantitative study and thematic analysis method has been used for qualitative part of this research. According to the descriptive statistical findings, respondents from Malaysian and Saudi Arabian oil and Gas industries are mutually considered Mechanical failure; Bad weather condition and pilot mistake are the major cause of offshore helicopter accidents with overall mean range 3.48 from Malaysia and 3.43 from Saudi Arabian respondent. Similarly, from qualitative results, respondent have highlighted mechanical and environmental hazard characteristics as a major cause of life-threatening accidents and injuries during offshore helicopter operation at targeted industries. Whereas, respondents from targeted industries highlights engineering and administrative controls as highly effective mitigating strategy to overcome potential hazards associated with helicopter operation.